Architectures and biogenesis of non-flagellar protein appendages in Gram-negative bacteria - Fronzes, Remi (Nature Publishing Group, 2008)
Bacteria commonly expose non-flagellar proteinaceous appendages on their outer surfaces. These extracellular structures, called pili or fimbriae, are employed in attachment and invasion, biofilm formation, cell motility or protein and DNA transport across membranes. Over the past 15 years, the power of molecular and structural techniques has revolutionalized our understanding of the biogenesis, structure, function and mode of action of these bacterial organelles. Here, we review the five known classes of Gram-negative non-flagellar appendages from a biosynthetic and structural point of view.